NutriCare: Aplikasi Pemantau Gizi Ibu Hamil untuk Menghindari Stunting dengan Memenuhi Kebutuhan Kalori dan Zat Besi - Maharani, Tarisyah Puan; Budhisantoso, Nugroho (Fakultas Teknik Universitas Persada Indonesia YAI, 2025)
Stunting in children under five, due to chronic malnutrition since in the womb, has an impact onchildren's health and cognitive development as well as the potential for long-term economic losses.In Indonesia, the prevalence of stunting will reach 21.6% in 2022. Iron and calorie deficiency inpregnant women is the main factor causing stunting, with 48.6% of pregnant women experiencinganemia. Many pregnant women lack easily accessible nutritional information. The Hilda AlnairaClinic in Koja, North Jakarta, faces challenges in providing manual nutritional recommendationsthat are inefficient and lack personalization. This research aims to develop the